Antioxidant Studies on Various Fractions of Methanol Extract of Terminalia bellerica Robx - SHERIN, LUBNA; SHUJAAT, SHAHIDA; BAQAI, FEHMIDA (Asian Journal of Chemistry, 2010)
Potential in vitro antioxidant activities of various fractions of crude methanol extract of Terminalia bellerica Roxb. fruits were evaluated using1,1-diphenyl-2-picryl hydrazyl (DPPH) radical scavenging, 2,2'- azinobis(3-ethylbenzothiazoline)-6-sulfonic acid (ABTS+) radical cation inhibition and antilipid peroxidation assays. The total phenolic and flavonoid content was also assessed. Results showed that ethyl acetate fraction (IC50, 3.09 μg/mL) possess potent DPPH radical scavenging activity, which was better than crude methanol extract (IC50, 7.72 μg/mL) and reference antioxidant, Trolox (IC50, 6.17 μg/mL). It showed better ABTS+ inhibition potential (IC50, 1.18 μg/mL) than crude extract (IC50, 2.27 μg/mL) and Trolox (IC50, 3.86 μg/mL). Highest antioxidant activity, as measured by the inhibition of lipid peroxidation was also offered by ethyl acetate fraction (IC50, 0.78 mg/mL). Maximum amounts of total phenolics and flavonoids were found in ethyl acetate fraction which correlates well with its antioxidant activity.